Prevalence of Cervical Intraepithelial Neoplasia (CIN) at Khulna Division of Bangladesh (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Back ground: Cervical cancer is the most common genital tract cancer and the important cause of cancer death among Bangladeshi women. Information about actual number of women living with preinvasive phase of cervical cancer and their diagnosis and treatment is limited. For strengthening the programme and policy for cervical cancer prevention , the baseline prevalence of cervical intraepithelial neoplasia ( CIN) need to be assessed.Methods: This population based study aimed to determine the prevalence of CIN among women of Khulna division of Bangladesh. Data has been collected from four upazila of four districts of Khulna division. VIA and colposcopy and histopathology was used for detection of cervical pre-cancers and early cancers among 1232 women of the mentioned population.Results: Crude prevalence of CIN was 5.84 %,CIN-II 1.1% and CIN- III .73% in colposcopically directed biopsy. Ninety two participants with CIN received treatment at the Colposcopy Clinic of Obstetrics and Gynaecology department of Khulna Medical College Hospital (KMCH).Conclusion: This population based prevalence study of CIN and socio demography would have conducive effect on future cervical cancer prevention programme.Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 21-28